2021
DOI: 10.2478/aiht-2021-72-3377
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of occupational injuries among insured workers in Saudi Arabia between 2004 and 2016

Abstract: This is a retrospective analysis of annual reports on occupational injuries issued by the national social insurance agency of the Kingdom of Saudi Arabia (KSA) for the years 2004 through 2016. For each criterion we calculated an index based on the equation NY/Nref x100, where NY is the number of occupational injuries by a specific criterion in a specific year Y, and Nref is the number of injuries in the corresponding criterion in the reference year, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
4
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 16 publications
6
4
3
Order By: Relevance
“…Most of the injuries occurred on Sunday (the first day of the week in Bahrain) during the morning to afternoon hours. This is contrast with a study done in Saudi Arabia [17] which shares common cultural features and also has Sunday as the first working day of the week, where they found that most OIs occurred on Friday, which is a weekend. A study done in Turkey did find results similar to our study where the injuries occurred mostly during weekdays [25].…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Most of the injuries occurred on Sunday (the first day of the week in Bahrain) during the morning to afternoon hours. This is contrast with a study done in Saudi Arabia [17] which shares common cultural features and also has Sunday as the first working day of the week, where they found that most OIs occurred on Friday, which is a weekend. A study done in Turkey did find results similar to our study where the injuries occurred mostly during weekdays [25].…”
Section: Discussioncontrasting
confidence: 92%
“…The average length of stay for admitted patient was 8 days; other studies have also reported similar length of stay [10,19,26]. We found that manufacturing sector was the most commonly involved place of injury and this is in line with other studies [14,15,22] while other studies in GCC countries have reported construction sector as the most common place of OI [10,16,17]. The high number in manufacturing sector may be due to the fact that more people are employed in this sector in Bahrain.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations